INVESTIGATING TEACHER EDUCATION STUDENT-LEADERSâ€™ LANGUAGE METAFUNCTIONS IN SUPERVISORY COMMUNICATION - Bañez, Richard Mendoza (LLT Journal: A Journal on Language and Language Teaching, 2019)
As student-leaders are tasked to manage their respective student-organizations and protect the interest of whom they represent, they are expected to be fluent communicators. Hence, they need to be conscious of the way they generate their utterances and text by considering appropriate language functions. This survey type of research determined the extent of utilization of language metafunctions in supervisory communication by teacher education student-leaders in a state university at Malvar Batangas, Philippines. By employing a researcher-made questionnaire as a primary tool for obtaining data and applying appropriate statistical tools, the study revealed that the respondents utilized the ideational language metafunction as they influenced their fellow members to actively participate in activities initiated by their respective organizations through citing favorable and positive personal experiences, the interpersonal metafunction as they listened willingly to the suggestions and complaints expressed by their colleagues during various fora, and the textual metafunction as they solicited in a friendly manner their colleagues? suggestions for the improvement of their organizations during meetings. This study calls for enhanced supervisory communication skills among student-leaders through capacity building communication-related activities.DOI: 10.24071/llt.2019.220201